ANALISIS FAKTOR YANG MEMPENGARUHI MINAT NASABAH DALAM MEMILIH PRODUK SIMPANAN MUDHARABAH PADA BANK SYARIAH INDONESIA (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Zukhruf Dinnisa'Ul Furqana; Dwiyani Sudaryanti; Junaidi Junaidi (Universitas Islam Malang, 2022)
This study aims to determine the analysis of factors that influence customer interest in choosing mudharabah savings products at Bank Syariah Indonesia (a case study on students at the Islamic University of Malang). The population in this study were students majoring in Islamic banking FEB UNISMA class 2017, 2018, 2019, which was opened by 252 students. Samples were taken using purposive sampling method. The type of data used in this study uses multiple linear regression analysis techniques using the SPSS 25 program. The results of data analysis show that simultaneous analysis of factors that influence customer interest in choosing mudharabah savings products at Bank Syariah Indonesia (case study on students at the Islamic University of Malang) . Partially, the effect of profit sharing (X1) and location (X3) has a positive effect on customer interest in choosing mudharabah savings products at Bank Syariah Indonesia, while the effect of promotion (X2) has no effect on customer interest in choosing mudharabah savings products at Banks. Indonesian Sharia (a case study on students at the Islamic University of Malang).